Educational assortative mating and couples' linked late-life employment trajectories - Mark Visser; Anette Eva Fasang (Advances in Life Course Research, 2018)
In the context of population aging and growing numbers of older workers and older couples, this study examines how educational assortative mating earlier in life is associated with the division of paid work later in life between partners of opposite-sex couples in the Netherlands. We observe 20 years of linked partners' employment trajectories, when the male partners were aged 45–65. This longitudinal and dyadic perspective enables us to examine long-term patterns in couples' division of paid work, including the timing of retirement, beyond snapshots of the division of paid work between partners at specific ages. We consider labor supply and labor demand factors for older workers in connection to cumulative (dis)advantage over the life course and argue that educational assortative mating earlier in life reinforces social inequality between couples later in life. We innovatively apply multichannel sequence and cluster analysis using retrospective data from four waves of the Family Survey Dutch Population (FSDP) for the 1916–1957 birth cohorts. Findings support a typology of five groups of older couples: 1) high-status dual-earners, 2) low-status dual-earners, 3) high-status male breadwinners, 4) low-status male breadwinners and 5) dual-jobless/disabled couples. The male breadwinner clusters are more prevalent overall (53%), but even among these relatively old birth cohorts, a substantial share of couples is in a long-term, stable dual-earner arrangement later in life (41%). The majority of dual-earner couples consists of two high-status earners (24%). Multinomial logistic regression analysis supports that educational assortative mating earlier in life is associated with a polarization into resource-rich high-status dual-earners and resource-poor low-status male breadwinner couples later in life. We conclude that educational assortative mating sets in processes of cumulative (dis)advantage over the life course that leave an enduring imprint on couples' late-life employment trajectories.
Keywords: 330; Couples; Division of labor; Educational assortative mating; Life course; Retirement; Sequence analysis